Rain limits food supply of temperate breeding Barnacle Geese Branta leucopsis - van der Veen, I T; van der Jeugd, H P; Loonen, M J J E (Wildfowl, 1999)
The effect of rain growth rates of individually marked shoots of a preferred food plant, Festuca rubra, was studied in a temperate Barnacle Goose brood rearing area during three consecutive years. We found that grass growth declined to zero well before fledgling of the goslings during dry years, and that rain had an immediate short-term positive effect on grass growth, especially towards that end of the growing season. Experimentally we found some indication that water is limiting grass growth towards the end of the season. Besides that, there might have been an additional effect of adding droppings. Thus, rain is an important factor influencing grass growth rates, which in turn influence both quantity and quality of food plants. We propose such an effect as the mechanism explaining effects of rain on important life history parameters that have been documented earlier for this Barnacle Goose population, as well as in other herbivores.